New Perspectives in the Adaptive Assessment of Depression: The ATS-PD Version of the QuEDS - Spoto, Andrea; Serra, Francesca; Donadello, Ivan; Granziol, Umberto; Vidotto, Giulio (Frontiers in Psychology, 2018)
Measurement is a crucial issue in psychological assessment. In this paper a contribution to this task is provided by means of the implementation of an adaptive algorithm for the assessment of depression. More specifically, the Adaptive Testing System for Psychological Disorders (ATS-PD) version of the Qualitative and Quantitative Evaluation of Depressive Symptomatology questionnaire (QuEDS) is introduced. Such implementation refers to the theoretical background of Formal Psychological Assessment (FPA) with respect to both its deterministic and probabilistic issues. Three models (one for each sub-scale of the QuEDS) are fitted on a sample of 383 individuals. The estimates obtained are then used to calibrate the adaptive procedure whose performance is tested in terms of both efficiency and accuracy in a simulation study. Results indicate that the ATS-PD version of the QuEDS allows for both obtaining an accurate description of the patient in terms of symptomatology, and reducing the number of items asked by 40%. Further developments of the adaptive procedure are then discussed.